2019
DOI: 10.1038/s41541-019-0117-5
|View full text |Cite|
|
Sign up to set email alerts
|

HIV therapeutic vaccine enhances non-exhausted CD4+ T cells in a randomised phase 2 trial

Abstract: VAC-3S is a therapeutic vaccine comprising a highly conserved HIV-gp41 motif coupled with the CRM197 carrier protein. High levels of anti-3S antibodies (Abs) have been associated with improved protection of CD4 + T-cell survival. A previous phase 1 study demonstrated the safety of VAC-3S. This multicentre, randomised, double-blind, placebo-controlled phase 2 clinical trial enroled between January 2014 and March 2015 HIV-1-infected patients under ART with plasma HIV RNA levels below 50 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…The antigenicity of 3S or EC26 has been previously studied in French and German HIV-1 infected individuals and their immunogenicity has been tested in mice, nonhuman primates and humans 18 , 19 , 23 – 26 , 31 33 . Based on these results EC26 and, in particular, 3S are considered promising potential vaccine candidates 19 , 24 . However, these gp41 regions vary significantly between and within HIV-1 clades which may affect their antigenicity and immunogenicity 28 , 34 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The antigenicity of 3S or EC26 has been previously studied in French and German HIV-1 infected individuals and their immunogenicity has been tested in mice, nonhuman primates and humans 18 , 19 , 23 – 26 , 31 33 . Based on these results EC26 and, in particular, 3S are considered promising potential vaccine candidates 19 , 24 . However, these gp41 regions vary significantly between and within HIV-1 clades which may affect their antigenicity and immunogenicity 28 , 34 .…”
Section: Discussionmentioning
confidence: 91%
“…The 15-mer 3S peptide (aa 609–623) is located between heptad repeat 1 (HR1) and HR2, and contains the epitope 613-SWSNKS-618 21 24 . A single W-to-A substitution at position 614 originated peptide W164A-3S; anti-W164A-3S antibodies with neutralizing activity and conferring protection from CD4 + T cells depletion were detected in the sera of some HIV-1 patients 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wyjątek stanowią np. HIV albo choroby nowotworowe [88,89]. Beneficjenci szczepionek nie staną w marszu naprzeciw tych, którzy uważają się za ofiary szczepień.…”
Section: Kto Może Decydować O Szczepieniach?unclassified
“…From these data, the VAC-3S therapeutic vaccine was developed, comprising the 3S peptide coupled with the CRM197 carrier protein formulated in an aluminum salt adjuvant (licenced by Minka Therapeutics). Moreover, a multi-center phase 2, randomized, double-blind, placebo-controlled clinical study revealed that VAC-3S is safe, immunogenic, and associated in high responders with an increase in non-exhausted CD4 + T cells [58].…”
Section: Peptide-based Vaccination For Antibody Responses Against Hivmentioning
confidence: 99%